Exposure of a Dengue Vector to Tea and Its Waste: Survival, Developmental Consequences, and Significance for Pest Management - Dieng, Hamady; Tan Yusop, N.S.B; Kamal, N.N.B; Ahmad, A.H.; Ghani, I.A.; Abang, F.; Satho, T.; Ahmad, H.; Zuharah, W.F.; Majid, A.H.A.; Morales, R.E.; Morales, N.P.; et al. (American Chemical Society, 2016)
Dengue mosquitoes are evolving into a broader global public health menace, with relentless outbreaks and the rise in number of Zika virus disease cases as reminders of the continued hazard associated with Aedes vectors. The use of chemical insecticidesthe principal strategy against mosquito vectorshas been greatly impeded due to the development of insecticide resistance and the shrinking spectrum of effective agents. Therefore, there is a pressing need for new chemistries for vector control. Tea contains hundreds of chemicals, and its waste, which has become a growing global environmental problem, is almost as rich in toxicants as green leaves. This paper presents the toxic and sublethal effects of different crude extracts of tea on Aedes albopictus. The survival rates of larvae exposed to tea extracts, especially fresh tea extract (FTE), were markedly lower than those in the control treatment group. In addition to this immediate toxicity against different developmental stages, the extracts tested caused a broad range of sublethal effects. The developmental time was clearly longer in containers with tea, especially in those with young larvae (YL) and FTE. Among the survivors, pupation success was reduced in containers with tea, which also produced low adult emergence rates with increasing tea concentration. The production of eggs tended to be reduced in females derived from the tea treatment groups. These indirect effects of tea extracts on Ae. albopictus exhibited different patterns according to the exposed larval stage. Taken together, these findings indicate that tea and its waste affect most key components of Ae. albopictus vectorial capacity and may be useful for dengue control. Reusing tea waste in vector control could also be a practical solution to the problems associated with its pollution.